Assessment of effectiveness of extracapsular cataract extraction versus manual small incision cataract surgery: an observational study - Sakre, Mohin M.; Nizami, Sana; Singh, Ranjana; Raghavendra, Anuhya; Takalkar, Anant Arunrao (International Journal Of Community Medicine And Public Health, 2019)
Background: Dilemma of cost effectiveness of manual small incision cataract surgeries (MSICS) in the terms of training and equipment has been widely pondered upon in developing areas. Objective of the study is to compare the manual small incision cataract surgery and extra capsular cataract extraction. Methods: A prospective study was conducted among the IPD patients of the Ophthalmology Department of Khaja Bandanawaz Teaching and General Hospital, Kalaburagi, from June to December 2017. Statistical Analysis was performed using Microsoft Excel 2013, SPSS 23.0 and Chi-square test was performed. Results: Out of the 160 individuals who underwent extra capsular cataract extraction (ECCE), 06 (3.75%), 91 (56.88%) and 63 (39.37%) of the study subjects had poor (5/50), moderate (6/60-6/24) and good (6/18-6/6) visual acuity respectively. Highest incidence was that of lens prolapse (25%) and corneal complications (25%) in ECCE. Among the subjects who underwent MSICS, highest incidence of intra operative complication noticed was that of lens prolapse, iris prolapse and anterior chamber collapse, each at 20%. Conclusions: It was concluded that the restoration of visual acuity was fairly good and uniform in both the procedures. Certain intra operative complications such as lens prolapse, iris prolapse and anterior chamber collapse were noticed in MSICS and capsular flaps and vitreous loss were noticed only in ECCE.